2015
DOI: 10.1111/bjhp.12141
|View full text |Cite
|
Sign up to set email alerts
|

Managing chronic orofacial pain: A qualitative study of patients', doctors', and dentists' experiences

Abstract: Current management of COFP is ineffective and unsatisfactory for patients and practitioners, which impacts on their relationship. Fundamental barriers to accessing and implementing psychological interventions for COFP arise from ineffective communication between physicians and patients, and between medical and dental practitioners. Statement of contribution What is already known on this subject? COFP is characterized by persistent pain in the face, mouth, or jaws that are not the result of organic disease or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(111 citation statements)
references
References 55 publications
5
105
0
1
Order By: Relevance
“…reported that the knowledge of general dentists about TMJ disorders was insufficient and the level was lower than specialist dentists [31]. Peters et al , reported that although psychological factors play a role in chronic orofacial pains, treatments provided to patients are insufficient and limited to therapeutic interventions [32]. Alonso et al ., reported that the lowest level of self-assessment of students about chronic orofacial pain was related to treatment abilities of pain with psychological origins [25].…”
Section: Discussionmentioning
confidence: 99%
“…reported that the knowledge of general dentists about TMJ disorders was insufficient and the level was lower than specialist dentists [31]. Peters et al , reported that although psychological factors play a role in chronic orofacial pains, treatments provided to patients are insufficient and limited to therapeutic interventions [32]. Alonso et al ., reported that the lowest level of self-assessment of students about chronic orofacial pain was related to treatment abilities of pain with psychological origins [25].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer empirical studies include HCP experiences. Those that do highlight the emotional toll of treating patients with chronic pain; [29][30][31][32][33] 32,34 and not knowing the appropriate information to give patients. 29 The current study finds that these factors experienced by many patients and HCPs can also create barriers to successful selfmanagement.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…A guided self management intervention was developed based on CBT principles, using Medical Research Council (MRC) guidance for the development and evaluation of complex interventions (6,7).The intervention was developed using findings from a best evidence synthesis of 3 specially conducted studies (systematic review, (5) survey of dentists (8) and a qualitative study of dentists, GPs and patients (9). A full review of this process is available (10).…”
Section: Introductionmentioning
confidence: 99%